Implementasi Pendekatan Kontekstual untuk Meningkatkan Gairah Siswa dalam Pembelajaran Biologi di Madrasah Aliyah Negeri 02 Banyumas - Siti Nur Irhami (Institut Agama Islam Negeri Purwokerto, 2019)
Biology as a subject has different characteristics from other subjects taught in the madrasa. Biological objects in the form of living things are the main attraction that can attract the attention and interest of students to learn. Characteristics of Biology as a science are objects of study in the form of concrete objects and can be captured by the senses, developed based on empirical experience (real), have systematic steps that are standard, use deductive and inductive logical thinking, the results are objective or what they are and results in the form of generally accepted laws wherever they apply. Biology studies / studies living things with all their problems that are born and developed through observation and experimentation which are scientific work steps. Biological development can be seen from the number of objects observed and the increasing number of problems of living things that need to be experimented with. In order for the desire of the madrasa students to learn more about Biology, a learning approach that involves technological advancement is needed, one of which is by using learning media in the form of microscopes equipped with cameras, LCDs and projectors. Key words :Characteristics of Biology, learning media, madrasa. Abstrak Biologi sebagai sebuah mata pelajaran memiliki karakteristik berbeda dari mata pelajaran lain yang diajarkan di madrasah. Obyek biologi berupa makhluk hidup merupakan daya tarik tersendiri yang dapat menarik perhatian dan minat siswa untuk mempelajari.Karakteristik Biologi sebagai sains adalah obyek kajian berupa benda konkret dan dapat ditangkap indera, dikembangkan berdasarkan pengalaman empiris (nyata), memiliki langkah-langkah sistematis yang bersifat baku, menggunakan cara berpikir logis yang bersifat deduktif dan induktif, hasilnya bersifat obyektif atau apa adanya serta hasil berupa hukum-hukum yang berlaku umum dimanapun diberlakukan. Biologi mengkaji makhluk hidup dengan segala permasalahannya yang lahir dan berkembang melalui pengamatan dan eksperimen yang merupakan langkah-langkah kerja ilmiah. Perkembangan biologi dapat dilihat dari banyaknya obyek yang diamati serta semakin banyaknya permasalahan makhluk hidup yang perlu dieksperimenkan. Agar keinginan siswa madrasah semakin tinggi mempelajari Biologi maka dibutuhkan pendekatan pembelajaran yang melibatkan kemajuan teknologi, di mana salah satunya dengan menggunakan media belajar berupa mikroskop yang dilengkapi kamera, LCD dan proyektor.